Reducing Arsenic Concentration in Panax notoginseng via Contaminant Immobilization in Soil Using Fe–Ce Oxide. Issue 2 (1st March 2018) - Lin, Longyong; Zhong, Lirong; Yan, Xiulan; Fei, Yang
Abstract : Panax notoginseng (Burk.) F.H. Chen, a valuable Chinese medicine, is currently confronted with arsenic (As) contamination in China due to soil pollution. Our previous research demonstrated that Fe(0) and zeolite had a certain inhibitory effect on As accumulation in P. notoginseng . In order to further reduce As accumulation in the plant, a synthetic iron material (Fe–Ce oxide [FC]) with high As adsorption capacity was tested for As remediation. In the study, after FC was applied to the As‐contaminated soil, Panax notoginseng was planted in the soil. The As leaching behavior of the treated soil and As accumulation in P. notoginseng were evaluated. The results showed that FC immobilized As more effectively than Fe(0) and zeolite in soils with high As concentrations. When the FC dosage was 0.5 % (w/w), As concentration of P. notoginseng root (the main medicinal part) decreased by 56%, and root biomass increased by 55%. Results indicated FC could reduce the non‐specifically adsorbed As fraction (F1) and specifically adsorbed As fraction (F2) by 22 to 31% and 5 to 17%, respectively, thus reducing the toxicity characteristic leaching procedure leachable As concentration by 41 to 67%. The finding of an iron plaque coating on the plant root and its function as a barrier to As uptake by P. notoginseng is reported here for the first time. The occurrence of iron plaque led to a reduction in As concentration in the phellem and xylem–phloem by 66 to 80% and 43 to 70%, respectively. Our findings will help in developing As contamination control in areas where P. notoginseng is planted and set a foundation for a FC‐based As immobilization technology. Core Ideas: Application of Fe–Ce oxide could guarantee Panax notoginseng growth and reduce its As uptake. Fe–Ce oxide could immobilize more available As in soil to reduce the amount of plant‐absorbable As. Iron plaque on the root was an important barrier for As uptake by Panax notoginseng . Durable effect of As immobilization by Fe–Ce oxide was better than previous reported amendments.